ABCD1 deletion‐induced mitochondrial dysfunction is corrected by SAHA: implication for adrenoleukodystrophy. (13th January 2015) - Baarine, Mauhamad; Beeson, Craig; Singh, Avtar; Singh, Inderjit
Abstract X‐linked Adrenoleukodystrophy (X‐ALD), an inherited peroxisomal metabolic neurodegenerative disorder, is caused by mutations/deletions in the ATP‐binding cassette transporter (ABCD1) gene encoding peroxisomal ABC transporter adrenoleukodystrophy protein (ALDP). Metabolic dysfunction in X‐ALD is characterized by the accumulation of very long chain fatty acids ≥ C22:0) in the tissues and plasma of patients. Here, we investigated the mitochondrial status following deletion of ABCD1 in B12 oligodendrocytes and U87 astrocytes. This study provides evidence that silencing of peroxisomal protein ABCD1 produces structural and functional perturbations in mitochondria. Activities of electron transport chain‐related enzymes and of citric acid cycle (TCA cycle) were reduced; mitochondrial redox status was dysregulated and the mitochondrial membrane potential was disrupted following ABCD1 silencing. A greater reduction in ATP levels and citrate synthase activities was observed in oligodendrocytes as compared to astrocytes. Furthermore, most of the mitochondrial perturbations induced by ABCD1 silencing were corrected by treating cells with suberoylanilide hydroxamic acid, an Histone deacetylase inhibitor. These observations indicate a novel relationship between peroxisomes and mitochondria in cellular homeostasis and the importance of intact peroxisomes in relation to mitochondrial integrity and function in the cell types that participate in the pathobiology of X‐ALD. These observations suggest suberoylanilide hydroxamic acid as a potential therapy for X‐ALD. <boxed-text content-type="graphic" id="jnc12992-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Schematic description of the effects of loss of peroxisomal ATP‐binding cassette transporter D1 (ABCD1) gene on cellular Redox and mitochondrial activities and their correction by suberoylanilide hydroxamic acid (SAHA) treatment. Pathogenomic accumulation of very long chain fatty acids (VLCFA) as a result of loss of ABCD1 leads to dysfunctions of mitochondrial biogenesis and its activities. Treatment with SAHA corrects mitochondrial dysfunctions. These studies describe unique cooperation between mitochondria and peroxisome for cellular activities.